2012
DOI: 10.1007/s00383-012-3158-7
|View full text |Cite
|
Sign up to set email alerts
|

Single trocar retroperitoneoscopic assisted ipsilateral ureteroureterostomy for ureteral duplication

Abstract: The aim of this study is to present the technique and early outcomes of single trocar retroperitoneoscopic assisted ureteroureterostomy for ureteral duplication. The patient was placed in a lateral decubitus position. A skin incision of 11 mm width was made above the iliac crest. The operation was performed through single trocar with operating laparoscope. The two ureters were encircled with a vessel loop and exteriorized outside the retroperitoneal space via trocar incision. The pathologic ureter was divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…[1][2][3] Multiple authors have also reported the technique and results of minimally invasive approaches to ureteroureterostomy including laparoscopic, single site, and robot-assisted approaches for the repair of proximal and distal obstruction in the duplicated system, midureteral pathology, as well as for the management of reflux and ectopic ureters in a duplicated system. [5][6][7][8][9][10][11][12][13][14] A summary of the existing literature on laparoscopic and robotic ureteroureterostomy in children is provided in Table 2. A pooled analysis of all results reveals a mean operative time of 182 minutes (78-244 min) and a mean length of stay of 2.8 days (1-9 d).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Multiple authors have also reported the technique and results of minimally invasive approaches to ureteroureterostomy including laparoscopic, single site, and robot-assisted approaches for the repair of proximal and distal obstruction in the duplicated system, midureteral pathology, as well as for the management of reflux and ectopic ureters in a duplicated system. [5][6][7][8][9][10][11][12][13][14] A summary of the existing literature on laparoscopic and robotic ureteroureterostomy in children is provided in Table 2. A pooled analysis of all results reveals a mean operative time of 182 minutes (78-244 min) and a mean length of stay of 2.8 days (1-9 d).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our operative time included stent placement while the fastest reported operative time reported in the literature (78 min) was without ureteral stent placement. 10 The performing surgeon recorded his own time to secure the ureter during the laparoscopic-assisted ureteroureterostomy procedure, which averaged 10 minutes (6-15). In addition, 6/9 (67%) of patients in the laparoscopic-assisted group went home the day of surgery and the remaining three spent one night in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Operasyonu laparoskopik ya da robot yardımlı olarak üreterlerin distalinde de gerçekleştirmek olasıdır (22,23,24,27) . Ameliyatın anastomoz kısımlarının batın dışında gerçekleştirildiği laparoskopi yardımlı ve retroperitoneoskopi yardımlı şekilleri de tanım-lanmıştır (30,31) .…”
Section: İpsilateral üReteroüreterostomiunclassified